2021
DOI: 10.1186/s13643-021-01613-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-rape medicolegal service provision and policy in East Africa: a scoping review protocol

Abstract: Background Sexual and gender-based violence (SGBV) is an epidemic that continues to affect both men and women in East Africa. Despite the high prevalence of SGBV in this region, sexual offense policies are often unclear, poorly enforced, or completely lacking. When policies do exist practitioners who assist survivors in the aftermath of the violation often are unaware of them, or may not implement them for a host of reasons (e.g., culture, personal beliefs, and resource limitations). This scopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…Countries included in the studies were Zambia ( n = 7), Rwanda ( n = 3), Malawi ( n = 3), Uganda ( n = 1), Sudan ( n = 1), and Zimbabwe ( n = 1). This finding is similar to that of other reviews conducted in East Africa, which also found that the most studied country in the region regarding SV is Kenya (S. Rockowitz et al, 2021).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Countries included in the studies were Zambia ( n = 7), Rwanda ( n = 3), Malawi ( n = 3), Uganda ( n = 1), Sudan ( n = 1), and Zimbabwe ( n = 1). This finding is similar to that of other reviews conducted in East Africa, which also found that the most studied country in the region regarding SV is Kenya (S. Rockowitz et al, 2021).…”
Section: Resultssupporting
confidence: 91%
“…The provider will document the crime, the injuries, and forensic evidence on an official government form (i.e., the Post Rape Care form) (Olson et al, 2022). Moreover, survivors of SV must disclose to medical providers that they have been violated to receive free medical services (S. R. Rockowitz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We originally sought to review research on service provision as well as existing regulations and policies surrounding SGBV medical and legal services in East Africa ( Rockowitz et al, 2021a ); however, subsequent literature searches returned few academic papers on SGBV regulations and policies in East Africa countries. Per recommendations of Levac et al(2010) , to envision the intended outcome of the study while also considering the feasibility of the research, we modified our original research questions and focused solely on service provision in the region rather than service provision and policy.…”
Section: Methodsmentioning
confidence: 99%